Coexistence of vitiligo and psoriasis: three case reports - Bakar-Dertlioglu, Selma; Ucak, Haydar; Cicek, Demet; Bitiren, Muharrem (Turkish J Pediatrics, 2012)
Bakar-Dertlioglu S, Ucak H, Cicek D, Bitiren M. Coexistence of vitiligo and psoriasis: three case reports. Turk J Pediatr 2012; 54: 77-79. Vitiligo and psoriasis are both common diseases. However, coexistence of these two diseases is rare. The pathogenesis of the coexistence of vitiligo and psoriasis is still unknown. Herein, we report three children (11-year-old, 8-year-old, and 7-year-old females) who attended our Department of Dermatology with coexisting vitiligo and psoriasis.
Keywords: vitiligo; psoriasis; coexistence